Determining the impact of economic activiy in Asturias on greenhouse gas emissions - Margarita Argüelles; Carmen Benavides; Celia Bilbao; Emma Ramos (European Regional Science Association (ERSA), 2003)
To fulfil the requirements of the Kyoto Protocol, public authorities with responsibility for the environment, need to design and implement policies to reduce greenhouse gas emissions, whose pollution impact is highly relevant. Hence it is necessary to develop reliable data bases, indicators and tools in order to determine the reach of such an impact. In Spain, the Autonomous Communities have powers and responsibility for dealing with environmental affairs. Thus, the aim of this paper is the construction of an environmental Input-Output Table for the Regional Government of Asturias, with useful information with respect to environmental aspects of the regional economy. Concretely, the consequences of economic activity on the greenhouse gas emissions will be studied. The specific targets will be: to define and calculate the emission coefficients for every production sector and the final demand of the Asturian regional economy; to account for the quantities of the greenhouse gas emissions by sectors for a specified year; and to construct an environmental IO accounts system for Asturias starting from the pollution coefficients matrixes. Once these matrixes have been developed, it will be possible to carry out a conventional IO analysis, including the environmental aspects. As a result, the quantity of the pollutants generated directly in the economy by each of the production sectors and by the final demand will be determined, as well as the additional indirect emissions belonging to the output production. Finally, the multiplier analysis will be extended to obtain the induced effects resulting from consideration of household consumption, financed by incomes from the domestic production sectors, as endogenous.
Keywords: 330